An analysis on the existence of burnout among ophthalmology residents-in-training in Ospital ng Maynila. - Sia, Stelson L.
Burnout is defined as the constellation of emotional exhaustion, detachment and low sense of accomplishment.? Medical residency is expected to be miserable hence doctors fail to recognize and acknowledge the existence of burnout. This is a cross-sectional study which analyzes the existence of burnout among Opthalmology Residents at the Ospital ng Maynila. This study utilizes the Maslach Burnout Inventory and showed that the residents had an average degree of burnout with a strong correlation between emotional exhaustion and depersonalization (Pearson Coefficient 0.85). They were also shown to have a suboptimal score on the Ophthalmology In-Training Proficiency Examination (OPEX) compared to the national average, which was strongly correlated with the measurable aspect of personal accomplishment. A more comprehensive study should be conducted in the future so that the data can be used to improve physicians-in-training's health and well-being
Management study (MHA)--University of the Philippines Manila, 2013
Keywords: Burnout